Managing with integrity : an ethical investigation into the relationship between personal and corporate integrity - Chennattu, Augustine (Fortress Press, 2020)
"Managing with Integrity challenges the readers to explore different perspectives on and conceptions of corporate ethics. It is situated within the broader context of the emerging interests of the people of India to eradicate corporate unethical conduct. The massive protest against corporate unethical conduct and public opinion puts leaders, top managers and employees under strong social and political pressure. This book aims at articulating arguments for the necessity of incorporating personal integrity formation along with codes of ethical conduct to reduce unethical corporate activity more steadily and effectively. This book is an ethical guide for managers, employees, politicians, clergy, candidates for priesthood, and business students, equipping them to eradicate corporate unethical conduct from all spheres of life."--Publisher's description.